Resenha do livro: "State-building in Boom Times: commodities and coalitions in Latin America and Africa" - Makino, Rogerio (Conjuntura Austral, 2014)
Resenha do livro: "State-building in Boom Times: commodities and coalitions in Latin America and Africa", de Ryan Saylor. Oxford: Oxford University Press, 2014. ISBN: 978-0199364954.